2021
DOI: 10.18502/jimc.v3i4.5191
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Safety of Ovarian Preservation at Early Stage of Endometrial Cancer in Premenopausal Women

Abstract: Background: Endometrial cancer usually occurs at postmenopause stage of life but its incidence in younger patients is increasing in the last decades. The objective of the study was to evaluate the ovarian preservation in the early stage of endometrial cancer. Methods: In this cross-sectional study, 174 patients with endometrial cancer who underwent Total Abdominal Hysterectomy (TAH) and Bilateral Salpingo-oophorectomy in 5 years were included. Results: The results showed that 51.1% of the patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Cognitive-behavioral treatments not only reduce patients' anxiety symptoms but also significantly improve patients' quality of life in the long run (Kangas et al, 2014;Shirali et al, 2020a;Shirali et al, 2020b;Yarandi et al, 2021). In a meta-analytical study, Tao et al, (2015) also investigated the effectiveness of psychological interventions in reducing mental distress in cancer patients and showed that psycho-oncology interventions have a very high effectiveness on the level of anxiety of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive-behavioral treatments not only reduce patients' anxiety symptoms but also significantly improve patients' quality of life in the long run (Kangas et al, 2014;Shirali et al, 2020a;Shirali et al, 2020b;Yarandi et al, 2021). In a meta-analytical study, Tao et al, (2015) also investigated the effectiveness of psychological interventions in reducing mental distress in cancer patients and showed that psycho-oncology interventions have a very high effectiveness on the level of anxiety of patients.…”
Section: Discussionmentioning
confidence: 99%